2021
DOI: 10.1021/acs.macromol.0c02345
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Compatibilization in Ternary Polymer Nanocomposites: Comparing Theory and Experiments

Abstract: In this work, we examine binary and ternary nanocomposites of poly(methyl methacrylate) grafted silica nanoparticles (PMMA-NP), in poly(styrene-ran-acrylonitrile) (SAN), and poly(methyl methacrylate) matrices as a platform to directly probe governing parameters guiding phase behavior and nanoparticle assembly in composite materials. Through the addition of PMMA matrix chains similar in molecular weight to the grafted PMMA chains and significantly smaller than the SAN matrix chains, we observe increased nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(49 citation statements)
references
References 51 publications
7
42
0
Order By: Relevance
“…We attribute this increased miscibility window to a decrease in the PMMA molecular weight, namely, decreasing from 91 to 19 kg/mol. An analysis of this behavior was described along with a comparison with the PRISM theory in the work by Maguire et al Overall, this result indicates that dense polymer brushes grafted to NPs (0.7 chains/nm 2 ) exhibit enthalpic interactions comparable to their analogues in a polymer blend.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…We attribute this increased miscibility window to a decrease in the PMMA molecular weight, namely, decreasing from 91 to 19 kg/mol. An analysis of this behavior was described along with a comparison with the PRISM theory in the work by Maguire et al Overall, this result indicates that dense polymer brushes grafted to NPs (0.7 chains/nm 2 ) exhibit enthalpic interactions comparable to their analogues in a polymer blend.…”
Section: Resultsmentioning
confidence: 93%
“…The bulk phase diagrams of a PMMA (91 kg/mol)/SAN (118 kg/mol) blend and of a PMMA (19 kg/mol)-NP/SAN (118 kg/mol) PNC have been previously constructed using complementary techniques of cloud point, TEM, and small-angle X-ray scattering. , Figure a depicts the phase diagram of the polymer blend, PMMA/SAN, which exhibits a lower critical solution temperature (LCST) of 160 °C . The phase diagram of the PNC, PMMA-NP/SAN, is plotted as a function of PMMA-NP weight fraction in Figure b . Comparing Figures a,b shows that the phase boundaries for the PNC and the binary polymer blends are similar near the critical point with a shift toward lower PMMA (PMMA-NP) weight fractions.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the effect of the introduction of NPs on the phase behavior is weak and systemdependent as shown by a few phenomenological theories [26][27][28][29] and measurements. [30][31][32] Ginzburg 26 predicted the effect of nanoparticles on the phase separation of PNC blends. He showed in particular that a possible enthalpic compatibilizing effect of NPs is counterbalanced for larger particles (RNP > Rg of the chain) by the entropic penalty on the chain conformation.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature dependence of decomposition has also been studied by SANS and isotopic labeling, allowing comparison to the Ginzburg–Landau approach of phase transitions and identifying the limits of mean-field theories. , The phase diagrams of pure blends are thus relatively well described by mean-field theories of known limitations. On the other hand, the effect of the introduction of NPs on the phase behavior is weak and system-dependent, as shown by a few phenomenological theories and measurements. Ginzburg predicted the effect of NPs on the phase separation of PNC blends. He showed in particular that a possible enthalpic compatibilizing effect of NPs is counterbalanced for larger particles ( R NP > R g of the chain) by the entropic penalty on the chain conformation.…”
Section: Introductionmentioning
confidence: 99%
“…In a related system of polymer nanocomposites (PNCs) composed of a matrix polymer and added nanoparticles with grafted polymer chains, several theory and simulation studies have shown that by tuning the PNC design (shape and size of particles, grafting density, polydispersity) and/or graft–matrix chemistry, the underlying entropic and enthalpic driving forces can be tailored to favor particle dispersion in the matrix. In particular, these studies show that at high grafting densities, tuning the extent of interpenetration between graft and matrix chains (i.e., grafted layer wetting) is key to controlling the dispersion or aggregation of particles in the matrix. For PNCs with chemically similar graft and matrix chains, in the high-grafting-density regime, morphology is driven purely by entropic driving forces and the grafted layer wetting can be increased by choosing the matrix polymer chain length to be smaller than the graft polymer chain length, increasing the stiffness of graft and matrix chains, , reducing particle diameter relative to graft polymer chain size, or choosing graft polymers with dispersity in molecular weight. ,, On the other hand, in PNCs with chemically dissimilar graft and matrix chains, the enthalpic driving forces arising due to direct graft–matrix interactions can either cooperate or compete with entropic driving forces, causing the grafted layer wetting to also depend on the choice of graft and matrix chemistries. , These competing entropic and enthalpic driving forces for graft–matrix wetting/dewetting and particle dispersion/aggregation are also relevant for dense polymer solutions and formulations with functionalized particles.…”
Section: Introductionmentioning
confidence: 99%